An exploring study on the packaging of broadcasting table tennis matches - Zhou, Y.; Gao, M.; Zhang, Y. (Proceedings book of the 14th ITTF Sports Science Congress & the 5th World Racquet Sports Congress, Suzhou, May 23.-25. 2015, 2017)
Objective: The combination between sports and television creates a "win-win" situation, and this tightened combination has become a symbol reflecting the quality of a successful sport packaging. As a classic representative of sports that compete with a net in the middle of the court, table tennis is extremely competitive. Certainly, table tennis is deficient in its broadcasting packaging, especially in providing game stats, up till now, is still a relative blank: besides watching the match itself, what spectators get are simply game score and results through subtitles. However, broadcasting without subtitles can never be called a complete sport broadcast today. The current level of table tennis broadcast packaging still have great potential in improving the ornamental value, increasing watching focus and so on. Therefore, this research start from game stats, exploring and discussing the future development of table tennis broadcast packaging and conceiving some specific plans. Research methods: Employing the method of literature review, the method of video observation and method of statistics, this paper has taken the token examples of NBA`s and Tennis Grand Slams` packaging through the utilization of game stats as reference, exploring the future packaging plan for table tennis matches. Results and conclusions (1) Using game stats to serve for match broadcast complies with the trend of development in contemporary sports, raising the quality and ornamental value of sports matches, a trend which table tennis must grab, enhancing its development in this field. (2) The packaging of table tennis broadcast also needs to follow the popular model, using game stats accordingly for pre-match, during the match and after match packaging. (3) Pre-match packaging mainly provides recent statistics on matches of both sides, statistics of matches between the two opposing sides, so as to reflect their current status, advantages & disadvantages and technique features, suggesting watching focus and commentaries. (4) Packaging during the match generally needs to provide statistics promptly and properly, backing up the commentaries through graphs and subtitles. (5) For after match packaging, the key is to provide game stats through graphs and tables of this very match, reviewing the critical factors, leading the broadcasting to a wonderful end. Table tennis broadcasting employing game stats for its packaging has just reached its starting stage. This paper suggests chose high level world competitions as primary packaging targets, then promoting the use of game stats in more table tennis matches so its packaging level can be improved.